THE IMPORTANCE OF MINDFULNESS APPS FOR BOOSTING THE EFFICIENCY OF LEARNING: "CALM", "STOP, BREATHE AND THINK", "HEADSPACE", "SMILING MIND" (Konferensiyalar | Conferences, 2024)
The fast-paced academic environment of higher education institutions places significant cognitive and emotional demands on students. This often leads to heightened stress, decreased focus, and compromised learning efficiency. Mindfulness, the practice of cultivating nonjudgmental present-moment awareness, offers a promising approach to alleviate these challenges. This study investigates the specific impact of popular mindfulness apps – Calm, Stop, Breathe & Think, Headspace, and Smiling Mind – on university students' learning efficiency. The research employs a mixed-methods design, combining quantitative measures of academic performance, attention span, and self-reported stress levels with qualitative analysis of participants' experiences. Students engage in a 6-week guided mindfulness program using the selected apps, with pre- and post-intervention assessments. Additionally, focus groups explore students' perceptions of the apps' usability, preferred features, and perceived changes in their study habits and emotional regulation. Findings will illuminate how different mindfulness app elements, such as guided meditations, breathing exercises, and mood tracking, contribute to improved learning efficiency. The study further examines the optimal frequency and duration of app-based mindfulness practice for maximizing academic benefits. Implications for educators, students, and app developers will be discussed, highlighting the potential of mindfulness apps to enhance learning outcomes, promote well-being, and support student success within the demanding context of higher education.